2014
DOI: 10.1016/j.engstruct.2014.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Design of coupled wall structures as evolving structural systems

Abstract: Coupled wall (CW) structures are outstanding lateral load resisting systems that not only reduce the deformation demands on the building, but also distribute inelastic deformation both vertically and in plan, between the coupling beams and the wall piers. When subjected to large seismic loads, coupling beams may deteriorate relatively quickly exhibiting both strength and stiffness degradation. This results in a rapid evolution in the performance of the CW system from behaving as a coupled wall system to behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 15 publications
0
8
0
2
Order By: Relevance
“…In a perfectly coupled system, axial forces are induced in the adjacent piers and the resultant moment of the piers axial forces resists against the overturning moment. However, in linked piers, each pier works individually and significant reaction forces are induced in the columns(Eljadei and Harries, ). Thus, the actual force of the VBEs found in coupled frames is somewhere between the axial force of fully coupled piers and completely separate piers.…”
Section: Finite Element Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In a perfectly coupled system, axial forces are induced in the adjacent piers and the resultant moment of the piers axial forces resists against the overturning moment. However, in linked piers, each pier works individually and significant reaction forces are induced in the columns(Eljadei and Harries, ). Thus, the actual force of the VBEs found in coupled frames is somewhere between the axial force of fully coupled piers and completely separate piers.…”
Section: Finite Element Studymentioning
confidence: 99%
“…The main goal of introducing coupled piers is to reduce the inelastic peak and residual deformations among building components. Furthermore, the coupled walls can distribute the inelastic deformation, both vertically and horizontally, between the coupling members and the wall piers (Eljadei and Harries, ). They can also be useful in respect to architectural limits when mandatory passage ways or openings need to be put into the walls (Sabelli, ).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been employed as a key parameter in the design of coupled wall systems [Eljadei and Harries, 2014;Hung and Lu, 2015]. For example, in order to facilitate the preferred seismic performance, it is suggested that the suitable design values of CR be between 30% and 45% for short coupled walls and between 45% and 60% for tall ones [Hung and Lu, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…The CR is widely recognized as a critical factor affecting the seismic performance of a coupled wall system [Eljadei and Harries, 2014;El-Tawil et al, 2010;Chaallal et al, 1996;Hassan and El-Tawil, 2004;Harries et al, 2004]. It has also been employed as a key parameter in the design of coupled wall systems [Eljadei and Harries, 2014;Hung and Lu, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…Coupled shear walls with SLBs usually called hybrid‐coupled shear walls. Rational design recommendations on hybrid‐coupled shear wall structures were presented in various literatures . More specifically, SLBs were suggested to be designed with smaller yield drift to dissipate energy and sacrifice themselves to protect the whole structure from severe seismic damage or even collapse…”
Section: Introductionmentioning
confidence: 99%